THE EFFECTIVENESS OF SOME MEDICINAL PLANTS ON BODY PERFORMANCE, HEMATOLOGICAL, ILEUM MORPHOLOGY AND IMMUNE STATUE OF JAPANESE QUAIL - M, Mahbuba A.; Ab. Jabbar , A.; Mustafa, N. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigates and compares the effect of medicinal plants extract: Hero flowers (Alcea kurdica) in the north of Iraq, Thyme (Thymus bovie), and Bay leaf (Laurus nobilis) extract with two antibiotic drugs Rifaximine and Ranitidine in quail’s drinking water by emphasizing the productive performance, and physiological status of the quails at grower and developer stages till 10th weeks of age, a total of 90 quails were distributed into six treatments, each treatment with three replicates of 15 chicks in each. Data analysis showed significantly increased body weight gain (237.5, 224.1, and 234.9) g for Hero, thyme, and Bay leaf, respectively. In comparison with the control (188.3) g. quail’s drunk plant extract mixed water had better hematological and the ileum profiling (goblet cells numbers, Villus height, and Crypt depth) and significantly higher serum concentrations of total protein, globulin, and antibodies titers against some bird virus diseases in comparison with positive control. Also, significantly lower level of albumin, ileum content of E. Coli, and Enterococcus count in plant treated quails in comparison with the control T0.